Profile of Emotional Form of Students in Following Individual Counseling Services - Suryadi, Suryadi; Rahma Mulyani, Rila (Holistic Science, 2022)
This research was motivated by the presence of students who were anxious, afraid, to enter the guidance and counseling room but there were also students who spontaneously, enthusiastically entered the guidance and counseling room to perform individual counseling services. This study aims to determine: 1) Profile of the positive emotional form of students in participating in individual counseling services. 2) The form of negative emotions of students in participating in individual counseling services. This research is quantitative descriptive. The population in this study were students who had attended individual counseling services at SMK Negeri I Gunung Tuleh as many as 67 students. The sampling technique was carried out by total sampling. The number of samples in this study was 67 students. Research data obtained through a questionnaire. The data is processed using the percentage technique. The results of the study revealed that the emotional form of students in participating in individual counseling services at SMK Negeri I Gunung Tuleh, seen from: 1) The profile of students' positive emotional forms in participating in individual counseling services was in many criteria. 2) The form of negative emotions of students in participating in individual counseling services is in quite a lot of criteria